Size-Dependent Photophysical Behavior of Low Bandgap Semiconducting Polymer Particles - Virgili, Tersilla; Botta, Chiara; Mróz, Marta M.; Parrenin, Laurie; Brochon, Cyril; Cloutet, Eric; Pavlopoulou, Eleni; Hadziioannou, Georges; Geoghegan, Mark (Frontiers in Chemistry, 2019)
By ultrafast spectroscopy the photophysics of water and propan-1-ol suspensions of different poly[N-9′-heptadecanyl-2,7-carbazole- alt -5,5-(4,7-di-2-thienyl-2′,1′,3′- benzothiadiazole] (PCDTBT) (nano)particles has been studied of different molar mass and size. High molar mass polymer (HMM > 20 kg/mol) forms nanoparticles with around 50 nm diameter via mini-emulsion post-polymerization, while low molar mass (LMM < 5 kg/mol) polymer prepared by dispersion polymerization results in particles with a diameter of almost one order of magnitude bigger (450 nm ±50 nm). In this study, the presence of excited-states and charge separated species was identified through UV pump and visible/near-infrared probe femtosecond transient absorption spectroscopy. A different behaviour for the HMM particles has been identified compared to the LMM ones. The HMM particles exhibit typical features of an energetically disordered conjugated polymer with a broad density of states, allowing for delayed spectral relaxation of excited states, while the LMM particles show a J-aggregate like behaviour where interchain interactions are less efficient. Stimulated emission in the red-near infrared region has been found in the LMM particles resulted to be a more energetically ordered system